Clinical replicability of rehabilitation interventions in randomized controlled trials reported in main journals is inadequate - Negrini, Stefano; Arienti, Chiara; Pollet, Joel; Engkasan, Julia Patrick; Francisco, Gerard E.; Frontera, Walter R.; Galeri, Silvia; Gworys, Kamila; Kujawa, Jolanta; Mazlan, Mazlina; Rathore, Farooq A.; Schillebeeckx, Fabienne; et al. (Elsevier, 2019)
Objective: The objective of this study was to study if randomized controlled trials (RCTs) in rehabilitation (a field where complex interventions prevail) published in main journals include all the details needed to replicate the intervention in clinical practice (clinical replicability). Study Design and Setting: Forty-seven rehabilitation clinicians of 5 professions from 7 teams (Belgium, Italy, Malaysia, Pakistan, Poland, Puerto Rico, the USA) reviewed 76 RCTs published by main rehabilitation journals exploring 14 domains chosen through consensus and piloting. Results: The response rate was 99%. Inter-rater agreement was moderate/good. All clinicians considered unanimously 12 (16%) RCTs clinically replicable and none not replicable. At least one “absent” information was found by all participants in 60 RCTs (79%), and by a minimum of 85% in the remaining 16 (21%). Information considered to be less well described (8–19% “perfect” information) included two providers (skills, experience) and two delivery (cautions, relationships) items. The best described (50–79% “perfect”) were the classic methodological items included in CONSORT (descending order: participants, materials, procedures, setting, and intervention). Conclusion: Clinical replicability must be considered in RCTs reporting, particularly for complex interventions. Classical methodological checklists such as CONSORT are not enough, and also Template for Intervention Description and Clinical replication do not cover all the requirements. This study supports the need for field-specific checklists. © 2019 Elsevier Inc.